Analisis Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus Terhadap Pengalokasian Belanja Modal pada Pemerintah Kabupaten/ Kota di Provinsi Jawa Timur Tahun 2018 - Samudra, Edo; Sugeng, Sugeng (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
In decentralization, local governments are given the authority to manage their own government, including in terms of budget allocation. The allocation of capital expenditures is one of the problems faced by local governments. The capital expenditure budget allocation is lower when compared to other expenditures. The purpose of this study is to analyze the effect of Regional Taxes, Regional Levies, General Allocation Funds and Special Allocation Funds on the allocation of existing capital expenditures in the district / city governments in East Java in 2018. The data collection techniques used are library research and documentation. The sample used in this study includes 38 districts / cities in East Java Province and uses data that is already available on the website of the Ministry of Finance of the Republic of Indonesia. Then analyzed using multiple linear regression using SPSS version 21 software. The results of the study found that Local Taxes and Special Allocation Funds have a significant effect on the allocation of Capital Expenditures, while the Regional Levies and General Allocation Funds have no significant effect on the allocation of Capital Expenditures.